Hip Osteoarthritis and the Risk of All-Cause and Disease-Specific Mortality in Older Women: Population-Based Cohort Study - Barbour, Kamil E. (Arthritis Rheumatol, 2015)
OBJECTIVES: Determine the risk of all-cause and disease-specific mortality among older women with hip OA and identify mediators in the causal pathway. METHODS: Data were from the Study of Osteoporotic Fractures, a US population-based cohort study of 9704 white women, aged ≥65 years. The analytic sample included women with hip radiographs at baseline (N=7,889) and year 8 (N=5,749). Mortality was confirmed through October 2013 by death certificates and hospital discharge summaries. Radiographic hip OA (RHOA) was defined as having Croft grade ≥2 in at least 1 hip (definite joint space narrowing or osteophytes plus 1 other radiographic feature). RESULTS: Mean follow-up time was 16.1 ±6.2 years. Baseline and year 8 prevalence of RHOA was 8.0% and 11.0%, respectively. Cumulative incidence (proportion of deaths during study period) was 67.7% for all-cause mortality, 26.3% for cardiovascular disease (CVD) mortality, 11.7% for cancer mortality, 1.9% for gastrointestinal disease mortality, and 27.8% for all other mortality causes. RHOA was associated with an increased risk of all-cause (hazard ratio [HR], 1.14; 95% confidence interval [CI], 1.05–1.24), and CVD (HR, 1.24; 95% CI, 1.09–1.41) mortality adjusted for age, body mass index, education, smoking, health status, diabetes, and stroke. These associations were partially explained by physical function (mediating variable). CONCLUSION: RHOA was associated with an increased risk of all-cause and CVD mortality among older white women followed for 16 years. Dissemination of evidence-based physical activity and self-management interventions for hip OA in community and clinical settings can improve physical function and might also contribute to lower mortality.